PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - LIMUTIA DILLA (Jurnal Edukasi dan Penelitian Matematika, 2018)
The ability of conceptual understanding of mathematics is one of the learning objectives that are expected to be achieved by students. However, the conceptual understanding of mathematics of SMA Negeri 3 Pariaman students is not as expected. An alternative solution is to implement the Numbered Heads Together (NHT) type of cooperative learning model. The purpose of this research was to describe the differences in conceptual understanding of mathematics between the students who studied using the NHT type of cooperative learning model and those who studied using the conventional learning model, and to explain the development of positive attitudes of XII Social Science class students of SMA Negeri 3 Pariaman towards mathematics. The type of research is quasi-experimental and descriptive, with a Randomized Control-Group Only design. Sampling was conducted by using simple random sampling technique, and XII Social Science 3 as the experimental class and XII Social Science 4 as the control class. The research instrument used a test to measure the ability to understand the mathematical concepts in the form of essay and attitude questionnaires. Based on the results of data analysis, conceptual understanding of mathematics of the students who took part in learning using the NHT type of cooperative learning model is better than the students who studied with conventional learning model. It means that the NHT learning model has a positive effect on the students’ conceptual understanding of mathematics. In addition, the results of data analysis show that the development of positive attitudes of the students who followed the NHT learning model also increased. Keywords – Conceptual Understanding, Mathematics Learning, Numbered Heads Together (NHT), Positive